Providing medically tailored groceries and food resource coaching through the charitable food system to patients of a safety-net clinic in Dallas, Texas: a randomised controlled trial protocol - Michael Bowen; Sandi L Pruitt; Jaclyn Albin; Tammy Leonard; Willis Wong; Milette Siler; Carolyn Haskins; Jessica Turcios; Carla Pezzia; Alisha Ford; Bianca Schinzer; Kelseanna Hollis-Hansen (BMJ Open)
Introduction Linking patients living with chronic, diet-related diseases and food insecurity to charitable food assistance, medically tailored groceries (MTGs) and food resource coaching may empower patients to better manage their health in a way that is economically sustainable. This protocol paper describes the implementation of a study evaluating MTGs and food resource coaching in a food pantry setting.Methods and analysis A randomised controlled trial whereby patients of a safety-net health centre will be screened for The Emergency Food Assistance Program (TEFAP) and study eligibility. Eligible patients will be randomised to receive 4 months of usual pantry services (control), MTGs (intervention 1) or MTGs and food resource coaching (intervention 2) from a colocated food pantry. Measures collected monthly include adherence, fidelity and food selections from the pantry. Measures collected at baseline and follow-up include food and nutrition security, diet quality, household resiliency, loneliness and overall well-being. Qualitative interviews (n=60) will be conducted preintervention and postintervention. Analyses will include multiple regression models to analyse changes from baseline to follow-up as well as changes between groups over time. Deductive thematic analysis of qualitative data will be conducted.Ethics and dissemination This study was approved by the UT Southwestern Medical Center Institutional Review Board (STU-2023-1166) and the Parkland Health Office of Research Administration. This is protocol version two, modification approved on 3 June 2024. Findings will be disseminated through academic conferences, journals and to the public.Trial registration number NCT06242808.